Nyepi Holiday Package: Between Commercialization, Commodification and Revolting to Hegemony - Narottama, Nararya (E-Journal of Tourism; Volume 3 Number 1 (March 2016), 2016)
Nyepi is a sacred and a holy day for Hindus in Bali, Indonesia. It only happens once a year. At Nyepi time, for one day, all day activities in Bali are stopped, and the Hindus shall carry Catur Bratha PeNyepian, which consist of: Amati Karya (not working), Amati Geni (not light a fire), Amati Lelungan (not traveling) and Amati Lelanguan (not having fun/entertainment). Along with the rapid development of tourism in Bali, a Nyepi ritual is also inseparable from the shadow of tourism commercialization. In the last decade, more and more businesses are offering Nyepi holiday packages to tourists. Surely this is contrary to the real essence of Nyepi. The purpose of this research is to reveal what tourism through the commercialization of Nyepi holiday packages which has been done through the commodification of Nyepi as compared to its real meaning and how does Nyepi become a new hegemony in the sphere of social multiculturalism. This research approach is qualitative description, and the theorical used, among others: the commodification theory, the theory of hegemony and the theory of consumerism. The result show that the influence of commercialization and commodification of Balinese culture is an outcome of the advancement of tourism. Nyepi commodification occurs in the process of modernization, which is rooted in capitalism and the increasing of heterogeneity in Bali. This phenomenon appears as an attempt by revolts against prevailing hegemony of Nyepi in Bali.
Keywords: Nyepi, Holiday Package, Commercialization, Commodification, Hegemony, Consumerism